The Overview of Manufactured Systems Models - Tubychko, K.V.; Zaruba, V.Y.; Pignasty, O.M.; Khodusov, V.D. (Економічний вісник Донбасу, 2015)
The article provides an overview of the main models of manufacturing systems. Here a comparative analysis of different types of models and shows their applications. In this article A brief description of the main model parameters. The detailed analysis of the streaming models with the using of partial differential equations. In this article is their classification depending on the equation of state. We examined the cross-sectional and two-moment description of the production process. У статті наведено огляд основних моделей виробничих систем. Виконано порівняльний аналіз різних типів моделей і показано області їх застосування. Надана коротка характеристика основних параметрів моделей. Детально розглянуто потокові моделі з використанням рівнянь в частинних похідних. Проведена їх класифікація залежно від виду рівняння стану. Розглянуто одномоментний і двохмоментний опис виробничого процесу. В статье приведен обзор основных моделей производственных систем. Выполнен сравнительный анализ разных типов моделей и показаны области их применения. Дана краткая характеристика основных параметров моделей. Детально рассмотрены потоковые модели с использованием уравнений в частных производных. Проведена их классификация в зависимости от вида уравнения состояния. Рассмотрено одномоментное и двухмоментное описание производственного процесса.